(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
An effort has been made in this paper to show the importance of effective governance and leadership in universities for the development of any country. The investigation of the points of view in the field of university governance has expand to unmistakable quality, particularly considering the verifiable need to progress towards progressively effective organizations, associated with the desires that society has about them. The change of governance in higher education leads to change in the educational plans and other related changes, are the noteworthy changes that universities everywhere throughout the world are witnessing. The government of India needs to expand the spending on the education sector for the advancement of the nation, as taught work power impacts the development.